Potensi Objek Wisata Pemandian Air Soda Parbubu I Kecamatan Tarutung Sebagai Unggulan di Sumatera Utara - Yunvinus Molama; Maringan Sinambela; Wolter P. Silalahi (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2025)
This thesis aims to examine the potential of the Soda Water Bath Tourism Object located in Parbubu I Village, Tarutung District, as a leading destination in North Sumatra. The activity of swimming in this bathing object is the only source of natural soda water in Indonesia and there are only two in the world. The method used in this study is a descriptive qualitative approach with data collection techniques, namely observation, interviews and documentation. The results of this study found that the tourist attraction has the strength of the uniqueness of nature, as well as local cultural values. 1 This is the background to why the Parbubu I Soda Water Bath has its own appeal, and has great potential to become a leading tourist attraction. This confirms that this tourist attraction is the only one in Indonesia and one of two in the world that has a natural soda water source. The problems that arise are limited infrastructure, supporting facilities, and lack of promotion. The purpose of this study is to identify the potential, challenges, and development strategies so that this tourist attraction becomes a leading destination in North Sumatra 2.The second chapter discusses theories related to tourism potential, types of tourism, and superior tourism concepts. Parbubu I Soda Water is seen from the perspective of natural, cultural, health, and educational tourism. The theories that support the author are embedded in this chapter, and accompanied by references to expert theories and past studies show the importance of future tourism management and community involvement in tourism development projects with local potential. 3 descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research location is in Parbubu I Village, Tarutung District. Primary data was obtained directly from the community, tourism managers, and tourists. Data analysis uses the Miles & Huberman interactive model, including data reduction, data presentation, and drawing conclusions. 4 This describes the results of observations and analysis of potential, uniqueness, and obstacles in the field. The uniqueness of soda water as a natural attraction with a reddish color and therapeutic effects is the main selling point. Equipped with a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) which shows the strengths of this tourism, but also challenges in terms of infrastructure and promotion. Suggested strategies include facility development, promotion through digital media, local community involvement, and collaboration with the government to make soda water a sustainable leading tourist destination.